Elucidation of supply chain integration in halal food industry - Mohd Helmi Ali,; Syed Shah Alam,; Shifa Mohd Nor,; Syajarul Imna Mohd Amin,; Norasiah Omar, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Much has been written about the importance of supply chain integration in determining firm performance. Moreover, for halal food production that is depending upon the wholesomeness in the supply chain, the external integration is crucial. However, there are scarce literature and managerial guide that focus on supply chain integration in the halal food industry. The aim of this research is to provide empirical evidence in explaining supply chain integration in the context of the halal food industry through a survey from 275 firms. The results provide strong empirical evidence on integrative activities and supply chain integration practices of halal food firms in Malaysian. In addition, the paper offers propositions on how supply chain integration may play their role in contributing to performance enhancement in the complex halal food industry